Literature Study on Self-Regulated Learning in Science Learning of Elementary School Students - Aninda Wahyu Ramadhani; Ika Maryani; Rungchatchadaporn Vehachart (International Journal of Learning Reformation in Elementary Education, 2022)
The study was conducted to determine the trend of research topics for self-regulated learning science for elementary school students in 2017-2021. This type of research is a descriptive quantitative research using literature study analysis and bibliometric methods. The data collection process is carried out by conducting observations and documentation on the Google Scholar online database. The data analysis phase was applied Mendeley, Publish or Perish, and VOSViewer. Based on the analysis of 102 research publications, 46 topics emerged. Relevant topics that arise relating to self-regulated learning do not all have a high occurrence rate. Topics with high emergence include Self-regulated learning, Learning Outcomes, Critical Thinking, Scientific Literacy, Motivation, Problem Based Learning, Inquiry, and Discovery Learning. Topics with low emergence and opportunities for further research are Strategy, Learning Media, Science Process Skills, Self-Efficacy, Emotional Intelligence, Metacognitive Skills, and Peer Learning.